PENGUATAN GENDER DALAM PENDIDIKAN ISLAM - Abdul Gani Jamora Nasution (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2017)
Gender is understood as a social relation that is attached to the public as sex. This sometimes makes the dilemma of social conservatives-textual, understand that women simply put